PERAN MASYARAKAT DALAM PENGELOLAAN DAN PENGEMBANGAN TAMAN WISATA ALAM DI DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Abdul Latis; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in the village of Buluh Cina Siak Hulu District Kampar. The purpose of this research is to know the management and development of the Buluh Cina  Nature Park by the people of Buluh Cina  District Siak Hulu Kampar District. The focus topic of this research is to know the constraints in the management and development of the Buluh Cina Reed Nature Park by the people of Buluh Cina District Siak Hulu Kampar District. The samples in this study amounted to 5 people. The author uses qualitative methods and uses pusposive sampling technique. Data instruments are observations, interviews and documentation. From the research conducted, the authors found that the community together agreed that the main maintainer of the natural tourism of Buluh Cina is the local community. The government is asked only as a supervisor and community escort only in providing direction and ideas related to the management of tourism. In the management of waste and security, the people of Buluh Cina village have divided the tasks with their fellow communities. The community always asks for advice from the government, then from the government will be in the best possible planning that considers the aspects of the natural environment so that there is no destruction of the natural forest because of the development and conversion of nature. In addition researchers also found that there are several obstacles in the management and development of natural tourism of Buluh Cina, namely as follows: limitation in dissemination of information, from the description of the subject of research known that the government is less Pay attention to the promotion of Buluh Cina nature tourism. Lack of community participation in the development of Nature Park, from the research conducted found that the participation of young generation of the village of China Buluh in the development of tourism objects is still very low.  Keywords: Social Capital, Social Networking, Nature Tourism